Proceedings of the 8th International Conference on Attosecond Science and Technology - Argenti, Luca.; Chini, Michael; Fang, Li.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This open access volume brings together selected papers from the 8th International Conference on Attosecond Science and Technology. The contributions within represent the latest advances in attosecond science, covering recent progress in ultrafast electron dynamics in atoms, molecules, clusters, surfaces, solids, nanostructures and plasmas, as well as the generation of sub-femtosecond XUV and X-ray pulses, either through table-top laser setups or with X-ray free-electron lasers. In addition to highlighting key advances and outlining the state of the field, the conference and its proceedings serve to introduce junior researchers to the community, promote collaborations, and represent the global and topical diversity of the field.
Chapter 1. Single-cycle infrared waveform generation and control -- Chapter 2. Increase in Photon Flux of Attosecond Pulses -- Chapter 3. Bright coherent XUV generation in microfluidic glass devices for ultrafast x-ray spectroscopy -- Chapter 4. Attosecond Physics and Quantum Information Science -- Chapter 5. Dynamics via Attosecond Four-Wave Mixing -- Chapter 6. Optical control of autoionizing states in argon -- Chapter 7. Retrieving a Complex Molecular Structure from Laser-Induced Electron Diffraction using Ma-chine Learning -- Chapter 8. Imaging ultrafast Dissociation Dynamics: OCS & Roaming in Formaldehyde -- Chapter 9. Controlling the time evolution of electron-nuclei entanglement for steering vibronic coherences dynamics induced by short 1-2 fs optical pulses -- Chapter 10. An MQDT model for the description of time resolved pump probe experiments -- Chapter 11. ASTRA, A Transition Density Matrix Approach to the Interaction of Attosecond Radiation with Atoms and Molecules -- Chapter 12. Symmetry-protected chiral sensitivity in photoionization with bichromatic fields -- Chapter 13. Experimental investigation of topological property of degenereate singularities in rescattering processes -- Chapter 14. Simulating strong field tunnel ionization of molecules -- Chapter 15. Control of photoelectron-ion entanglement in attosecond laser-induced photoionization of H2 -- Chapter 16. Ultrafast Second-harmonic XUV Spectroscopy: A Novel Probe for Symmetry -- Chapter 17. From Ultrafast Light-Induced Currents to Spatially-Resolved Field Sampling -- Chapter 18. Attosecond core-exciton dynamics in wide-gap insulators -- Chapter 19. Polarization-Shaped Strong Field Control over Valley Polarization with Mid-IR Light -- Chapter 20. The Future of Attosecond Science.
Keywords: 9; 9; Physical chemistry; Telecommunication; Lasers; Spectrum analysis; Atomic and Molecular Structure and Properties; Physical Chemistry; Microwaves, RF Engineering and Optical Communications; Laser; Spectroscopy; Spectroscopy